Analysis of Talent Development Influence on Employee Productivity At HR Centre Bandung PT Telekomunikasi Indonesia 2011 - Ningrum, Yuni Eka Pradipta; Welly, John (The Indonesian Journal of Business Administration, 2012)
An asset of the company’s that is most important and valuable is its employees, and on the basis of these considerations PT. Telekomunikasi Indonesia designing a new training program called the Talent Development. Talent Development is intended for training employees in PT. Telekomunikasi Indonesia and held for 6 months. This final paper is focus to find the degree of influence on talent development towards the level of employee productivity and to find the backwards in the implementation of talent development at PT. Telekomunikasi Indonesia, and provide new solutions and implementation plans for improvements to the talent development program. Research methodology used in this study is quantitative and qualitative by distributing questionnaires to 100 employees and also through interviews with some of the relevant manager. In this case, the main problem lies in the methods of talent development that according to questionnaires, the participants felt boring and monotonous so they cannot absorb the material that had been presented well. And the proposed solution is to add talent mapping program and also add some new learning methods such as role play, case studies, rolling assignment, and others which the learning process is not only done in the classroom but also outside the classroom or in work situation directly. Key words: PT. Telekomunikasi Indonesia, Talent Development, Employee Productivity